Challenges of hybrid working in the Sub-Saharan mining industry - Dube, Miriam (University of the Witwatersrand, Johannesburg, 2023)
The Covid-19 pandemic accelerated the shift to hybrid working models. Several industries especially in information technology had started implementing the different working models and post Covid-19 more and more industries started adopting the hybrid working models. Mining companies resorted back to the traditional on site in office working however this won’t be long as research indicates that more employees are opting for flexibility that comes with hybrid work models. The future of work theme is receiving a lot of attention because of how technologies through the fourth industrial revolution (4IR) will change how we work. To facilitate a smooth transition to hybrid working models mining companies in Sub Sahara Africa (SSA) must address challenges that impede hybrid working models. During Covid when employees worked remotely mining companies experienced challenges which include poor infrastructure that did not support working from home, employees failing to use the available technology and some social impacts related to work life balance. Existing research also indicates the challenges of hybrid working models; however, it only covers certain industries and continents. The challenges ultimately affected the productivity of the employees, and the mining companies were forced to revert to the traditional working model. As far as we know, no previous research has investigated the challenges for mining companies in SSA. The study seeks to determine the challenges of hybrid working models in the mining industry how the mining companies can navigate through these challenges as they prepare for the future of work. The study has significant benefits to the mining organisation and its managers as it will assist them in identifying challenges of hybrid working and formulating means of embracing this the future of work. The self-determination theory (SDT) and resource-based view theory (RBV) frameworks were used to link existing knowledge to this research. Qualitative research was used to collect, process, and analyse the data for this research. Through in-depth interviews of participants in Ghana, South Africa Tanzania and Guinea, the researcher formulated themes that enabled the analysis of the findings. The research revealed the challenges of hybrid working models in SSA mining industry and how management could navigate these. There is opportunity for further research, and all this is outlined in this research.
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2023
Keywords: Hybrid working; Remote working; Technology; Infrastructure; Future of work; UCTD; SDG-15: Life on land